Disruptive technologies of the globalization process (2019)
For the writing of this book, fourteen recognized Latin American specialists were invited to cover nine fundamental topics. Five authors are Mexican, seven Colombian and two North American. Their contributions are the result of their academic and professional experience in the areas treated by each one of them. However, as is proper to the bibliography of the case, this first volume of the collection Pensamiento global does not cover the totality of topics that, due to its vertiginous dynamic, surpasses any editorial attempt in this regard. For this reason, this contribution of the Centro de Pensamiento Global (CEPEG) has as its main objective the didactic disclosure of one of the most complex trends of the current globalization process. Its content and language combine the purely technical with the properly informative, in order to reach the widest and most diverse audience. As it is noticed at the beginning of the book, the ‘disruption’ itself is not an economic and technological phenomenon that would have appeared with the current globalization process.It simply took an unusual dynamic that in some cases --such as that of “artificial intelligence” (AI) -- seems to augur a human future that is certainly unpredictable. Without being able to predict the many possible futures of that post-global humanity, this book collects many of these concerns and suggests valid options for reflection.